Aggregating Labour Supply and Feedback Effects in Microsimulation - Creedy, J.; Duncan, Alan (The Centre for Labour Market Research, Curtin Business School, Curtin University of Technology, 2005)
This paper explores an extention of behavioural microsimulation modelling so that third round effects of a policy change can be simulated. The first round effects relate to fixed hours of work, while second round effects allow for changes in desired hours of work at unchanged wages. Third round effects allow for endogenous changes to the distribution of wage rates resulting from the labour supply responses to tax changes. This is achieved using the concept of an aggregate ‘supply response schedule’, which identifies the extent to which average labour supply responds to a proportional change in wage rates. The third round effect is obtained after re-running a micro simulation model with a suitable modification to individuals’ wage rates. The method is illustrated using the MITTS behavioural microsimulation model.